Risk factors for decreased bone mineral density in men with type 2 diabetes. - Olga N. Fazullina; Anton I. Korbut; Maksim V. Dashkin; Vadim V. Klimontov (Сахарный диабет)
BACKGROUND: Type 2 diabetes and osteoporosis are widespread diseases in the middle-aged and elderly people. Most studies of osteoporosis in patients with type 2 diabetes have been performed in women; meantime risk factors for lowering bone mineral density (BMD) in men have been little studied.AIMS: to identify risk factors for decreased BMD at the lumbar spine, femoral neck and forearm in men with type 2 diabetes.METHODS: Eighty two men from 50 to 75 years old, with duration of diabetes for at least one year, were included in the study. Individuals with known risk factors for secondary osteoporosis were not included. Twenty-three men with normal BMD having no diabetes or obesity were acted as control. The T-score at the lumbar spine, femoral neck and forearm of a non-dominant arm, as well as body composition parameters, were evaluated by dual-energy X-ray absorptiometry. The levels of hormones that affect bone metabolism (parathyroid hormone, free testosterone, 25-OH vitamin D) were measured in blood serum by ELISA. Risk factors for reducing BMD were identified using multivariate regression analysis and receiver operating characteristic (ROC) curves.RESULTS: Among patients with diabetes, 49 individuals had normal BMD and 33 showed decreased T-score values (<-1 SD). Free testosterone <5.92 pg/ml was predictor for decreased BMD at the lumbar spine (OR=4.4, p=0.04). For femoral neck, the risk factors were body weight <95.5 kg (OR=2.8, p=0.04), total fat mass <27 kg (OR=3.3, p=0.03), truncal fat mass<17.5 kg(OR=4.5, p=0.006), android (central abdominal) fat mass <3.2 kg(OR=4.0, p=0.01), gynoid (hip) fat mass <3.5 kg(OR=3.3, p=0.02), and lean mass <59 kg(OR=3.0, p=0.04). Risk factors for reduced BMD at the forearm were diabetes duration>15.5 years (OR=3.7, p=0.03) and HbA1c <8.15% (OR=3.8, p=0.03). Parathyroid hormone and 25-OH-vitamin D did not predict BMD independently.CONCLUSIONS: In men with type 2 diabetes, low free testosterone is a risk factor for decreased BMD in the lumbar spine, and diabetes duration is a risk factor for decreased BMD in the forearm. The presence of obesity is associated with an increase in BMD in the femoral neck; a high HbA1c is associated with an increase in BMD in the forearm.